2017
DOI: 10.1177/2042098617702615
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for adverse drug reactions in pediatric inpatients: a systematic review

Abstract: Background:The main objective of the present systematic review is to identify potential risk factors for adverse drug reactions (ADRs) through prospective cohort studies in pediatric inpatients. Methods: The data search was done in the following electronic databases PubMed/MEDLINE; Scopus; LILACS and Web of Science from the earliest record until 31 May 2015. Two reviewers independently screened each study and one of them assessed the methodological quality according to the Newcastle-Ottawa scale for cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
(142 reference statements)
1
22
0
1
Order By: Relevance
“…The occurrence of ADEs is associated with both patient characteristics and their health care utilization. With regard to risk factors associated with ADEs in pediatric patients, significant differences have been found in terms of the number of drugs 14 , length of hospital stay 15 , use of antibacterial 15 and general anesthesia 16 . However, such findings are not always consistent; while some studies found that gender was not significantly associated with ADEs 17 , a study also found that males were at higher ADEs risk compared to females 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of ADEs is associated with both patient characteristics and their health care utilization. With regard to risk factors associated with ADEs in pediatric patients, significant differences have been found in terms of the number of drugs 14 , length of hospital stay 15 , use of antibacterial 15 and general anesthesia 16 . However, such findings are not always consistent; while some studies found that gender was not significantly associated with ADEs 17 , a study also found that males were at higher ADEs risk compared to females 18 .…”
Section: Introductionmentioning
confidence: 99%
“…The main risk factor for adverse drug reaction occurrence in the pediatric population is the increase in the number of prescription drugs (11). In this study, the number of patients prescribed two or more drugs were 510 among 1500 prescriptions; 253 of these (49.6%) included 2 drugs, 228 (44.7%) included 3-4 drugs, and 29 (5.6%) included ≥5 drugs.…”
Section: Discussionmentioning
confidence: 77%
“…Concepts and terms established by the WHO9 were the reference base for the development of DOMAIN 1 . Several authors discussed the risk factors for the development of ADRs in Paediatrics, among them the exposure to multiple drugs, lack of defined doses for this age group, inadequate frequency, drug administration, period of permanence at the hospital, liver and kidney disease or immaturity and use of off label drugs 6 16–19. Studies show that the drug groups that promote ADRs in Paediatrics most are antibiotics and vaccines, mainly as dermatological reactions 20–23…”
Section: Methodsmentioning
confidence: 99%